Nomenclature for the KIR of non-human species - Robinson, J; Guethlein, L; Maccari, G; Blokhuis, J; Bimber, B; De Groot, N; Sanderson, N; Abi-Rached, L; Walter, L; Bontrop, R; Hammond, J; Marsh, S; et al. (Springer Verlag, 2018)
The increasing number of Killer Immunoglobulin-like Receptor (KIR) sequences available for non-human primate species and cattle has prompted development of a centralized database, guidelines for a standardized nomenclature, and minimum requirements for database submission. The guidelines and nomenclature are based on those used for human KIR and incorporate modifications made for inclusion of non-human species in the companion IPD-NHKIR database. Included in this first release are the rhesus macaque (Macaca mulatta), chimpanzee (Pan troglodytes), orangutan (Pongo abelii and Pongo pygmaeus), and cattle (Bos taurus).